Efficacy of Trichoderma Strains as Biotic Inducers against Alternaria Leaf Spot of Cauliflower - Sharma, Shalini; Sharma, Monica; Nughal, Jyoti; Sharma, Amit (International Journal of Bio-resource and Stress Management, 2024)
Alternaria leaf spot is one of the most destructive disease and cause huge economic losses in cauliflower. In the quest of eco-friendly disease management against Alternaria leaf spot of cauliflower, four isolates of Trichoderma, namely T. viride, T. harzianum I-6 strain, T. harzianum IMQ-8 and T. koningii were evaluated for their antagonistic potential against Alternaria leaf spot disease of cauliflower during the year 2020 at the College of Horticulture and Forestry, Neri, Hamirpur, Himachal Pradesh. In a dual culture assay, T. harzianum I-6 strain inhibited the mycelial growth of Alternaria brassicicola by 80.64%, followed by T. viride (78.49%). Root dip treatment of cauliflower seedlings with T. harzianum I-6 strain was found to be most effective in plants challenged with the pathogenic fungus i.e. A. brassicicola and resulted in a reduction in disease incidence and disease severity of 32.70% and 40.00%, respectively compared to pathogen-challenged control plants. It was followed by IMQ-8 strain of T. harzianum with 29.49 and 34.73% reduction in disease incidence and disease index, respectively. T. koningii was least effective against the disease. Among all Trichoderma treatments, the maximum plant weight of 6.84 g plant-1 was obtained by using T. harzianum I-6 strain, followed by T. harzianum IMQ-8 strain, T. viride and T. koningii with 6.45, 5.62 and 4.33 g plant-1, respectively. In comparison, plants inoculated with the pathogen weighed 3.72 g plant-1. Hence, seedling treatment with T. harzianum has the potential for eco-friendly management of Alternaria leaf spot of cauliflower.